Evaluation of English Learning Based on E-Learning as Media in SMA Negeri 1 Kawangkoan - Noldy Pelenkahu; Tini Mogea; Triesye A. Laloan (Journal of English Language Teaching, Literature and Culture, 2022)
Global demands require the world of education to always and constantly adapt technological developments to efforts to improve the quality of education. The use of online learning or e-learning as a learning media helps to improve the quality of education. Although in practice there are advantages and disadvantages to implementing e-learning in learning. The aim of this study was to evaluate English learning based on e-learning as media in SMA N 1 Kawangkoan. Uneven internet access is a fundamental problem faced in the implementation of e-learning. As stated by (Mutia & Leonard, 2013) that to get an effective e-learning process, students and teachers must have good devices and internet access. Furthermore, the application of e-learning can result in the interaction between students and teachers being not warm. The use of electronic media in this case social media made a distance in communication between students and teachers. And teachers found a cultural scrape in the way students communicate with teachers in inappropriate language, such as communicating with peers. Not pay attention to the time in contact with the teacher and students unknow the teacher who has taught.